Machine Learning of ZnO Interaction with Immunoglobulins and Blood Proteins in Medicine. (16th March 2022) - Qader Osman, Nasreddin Abdel; Al-Ziyadi, Shatha Hallal; Alazzam, Malik Bader; Alshawwa, Samar Zuhair; Rahman, Md Adnan
Abstract : Toxoplasmosis is a zoonotic illness caused by Toxoplasma gondii . Those with a normal immune system normally recover without treatment. Immunocompromised individuals and pregnant women must be treated regularly. Toxoplasmosis is a serious illness that may reactivate in immunocompromised patients. A retrospective study using machine learning of toxoplasmosis patients at Government Fever Hospital in Gorantla, Guntur, India, included 25 women, eight of whom were pregnant. These included sex, age, symptoms and side effects, pregnancy, ophthalmic, and antitoxoplasmosis titers, and treatment regimens. Protease mobility and specific activity were increased in toxoplasmosis-infected women's sera, although not significantly ( p= 0.05). However, there was no discernible decline. The impacts of nanoparticle impact demonstrated a 52.24 percent drop in compound concentration in the presence of zinc nanoparticles, whereas the effect of ZnO nanoparticles was 51.37 percent. Zinc nanoparticles lowered IgA, IgG, and IgM levels in the eye.